Explorations of Three Rock Art Sites in Northwestern Tigray, Ethiopia - Tekle Hagos (Ethiopian Journal of the Social Sciences and Humanities, 2019)
This article presents the result of archaeological reconnaissance carried in 2001 and 2004 with the support of the Authority for Research and Conservation of Cultural Heritage in the districts of Tselemti and Tahtay Koraro in North western Tigray Administrative Zone. The objective of the research was to explore and document foot prints of ancient humans in the northern western periphery of Ethiopia. The study resulted with the discovery of three rock-art sites dating between 5000 BP and 2000 BP. The paintings of these rock art sites portray domestication scenes of cattle, sheep and goat. Thus, they can be categorized under the two phases of Dahthami and Surre-Hanakiya of the Ethio-Arabian Styles. They furnish an evidence of contacts between the populations of Ancient Sudan, South Sudan, Egypt and those of the Northern Horn in the aforementioned period.